Identifying Trends in the Study of Gender in Science, Technology, Engineering, and Mathematics (STEM) Programs - Pineda, Vanessa; Gallegos, Ada; Valencia, Jackeline; Valencia-Arias, Alejandro; Montoya Benitez, Alber Oswaldo; Ospina Cifuentes, Bayron Jesit (Universitas Negeri Semarang, 2025)
In recent years, Science, Technology, Engineering, and Mathematics (STEM) education has gained increasing importance in response to changes driven by evolving social dynamics, emphasizing the need for professionals equipped with skills and knowledge to navigate the demands of modern society. However, the gender gap in STEM fields remains a widespread concern, primarily due to the underrepresentation of women. To address this, different strategies have been developed to encourage greater female participation in these areas. These strategies include promoting a greater representation of female mentors, implementing measures to eliminate discrimination, fostering a balance between personal life and work, and ensuring equitable conditions in promotions and salary allocation. Against this backdrop, the present study aims to identify research trends in STEM from a gender perspective by conducting a bibliometric analysis using the PRISMA 2020 methodology. The results reveal an exponential increase in scientific output on this topic, with a peak in publications occurring in 2022. Among the key themes emerging from the literature are persistent gender disparities, the relevance of self-efficacy, and the role of intersectionality in shaping women’s participation in STEM. Understanding why more women—and especially women of color—do not pursue or work in STEM disciplines is a concern from the standpoint of global diversity, particularly in the United States, where significant inclusion gaps remain. Furthermore, despite improvements in female representation, barriers related to retention and professional advancement persist. Overall, this analysis provides new insights into the thematic evolution and emerging directions of research at the intersection of gender and STEM.